EMERGING ISSUES AMONG WOMEN EMIRATI ENTREPRENEURS: A RESEARCH AGENDA - Mulnix, Michael William; Beede, Park; López-Mulnix, Esther Elena (European Scientific Journal, ESJ, 2014)
Entrepreneurship and new business development in the small and medium enterprise (SME) sector is a growing area of emphasis in the UAE. As highlighted in the recent Global Entrepreneurship Monitor (GEM) Report on Entrepreneurship, a substantial policy initiative exists in the UAE to encourage SME development through a broad array of business initiatives. As one outcome of the overall assessment, a major policy was recommended encouraging increased support for Emirati women entrepreneurs (GEM 2009). However, developing and launching a new business start-up is often a daunting task for an aspiring entrepreneur. Many of the key skills necessary to run an independent business—such as finance, marketing, family support and operational logistics—can present challenging barriers to long-term success. Our research is intended to increase the amount of empirical information related to the leadership skills and overall self-actualization of successful Emirati women entrepreneurs. We will examine issues that Emirati women face in their daily lives, how they view entrepreneurship as related to family demands and values, and how they work within the community to overcome obstacles and become successful business leaders. A key research question guiding the study is: How does a developing economy support entrepreneurial activities and development of women-run family businesses without compromising family life and cultural values? Through a comprehensive qualitative study, our research agenda will identify key factors associated with building successful family businesses in the UAE. Eventual results of this research will lead to initiatives encouraging SME development by women in the UAE with policy implications for the broader GCC region.